A Performance Analysis of the Dbms – MYSQL Vs POSTGRESQL - Svetlana Andjelic; Slobodan Obradovic; Branislav Gacesa (Communications - Scientific letters of the University of Zilina, 2008)
Modern communications among business subjects imply an exchange of a lot of data and information. To enhance that process in all its aspects, electronic data storing and processing is mandatory and enabled by an application of a DBMS (Date Base Managment System). This paper shows the performances analysis of the two most popular open source DBMSs - MySQL and PostgreSQL. First, some characteristics of these DBMSs are shortly described. Then the applied procedure of the performed testing is described. That is, the query (select, insert, delete and order by) execution times were measured for the both DBMSs mentioned, and the results shown in tabular and graphical forms. The goal of this paper is to make the choice of an adequate DBMS easier for future users.